Criminal Policy in Fiqh Jafari - . Noori Sharhan Katie ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The statement of the linguistic and legal terms of the vocabulary searched for in the title of the research, which is political and felony, including clarifying the area of ​​emptiness in which the jurisprudence moves to fill that vacuum jurisprudence through the ability of the jurisprudent to derive the legal provisions of the detailed evidence. - Including a statement of the characteristics of the Islamic ruling and its origin put up by God and that its legitimacy and consideration belongs to God to legislative and that in the best legal systems to regulate social relations and ensure interests and the removal of evil. - Including reference to the policy of prohibition at the doctrine of Jaafari and that the reasons for the prohibition come from the responsibility of man for his actions and deeds because he is chosen for his actions and a choice.